ADULT PATIENTS WITH CHRONIC PURULENT HAYMORITIS ARE INDICATORS OF CELLULAR IMMUNITY. - Tairova S.F; Nuraliev N.A (Scholar Express Journals, 2022)
In today's day, Clinical Immunology shows its potential to "recognize" pathogenic and conditionally pathogenic microorganisms in the formation of an adequate and effective immune response, which is carried out by elamination of the causative agent of the disease and the preservation of immune memory. Pathogens, in turn, try to avoid the effects of the immune system with their high level of variability and flexibility, the properties of being able to multiply quickly and in large quantities. This is due to the fact that in subsequent years, various changes in the relationship between different pathogens and the body's immune system occur, and the number of resistive strains is increasing.
Keywords: haymorites; cell immunity; microorganisms